Respuesta :
Answer:
The error is in step 3. You cannot use a property of logarithms to prove that same property.
Step-by-step explanation:
Here we the proof of the quotient rule as
If Logₐx = M and Logₐy = N
Then x = [tex]a^M[/tex] and y = [tex]a^N[/tex]
x ÷ y = [tex]a^M[/tex] ÷ [tex]a^N[/tex] = [tex]a^{(M-N)}[/tex]
Take log of both sides we get
Logₐ(x÷y) = Logₐ[tex]a^{(M-N)}[/tex]
Logₐ(x÷y) =M-N logₐa
Logₐ(x÷y) =M-N
∴Logₐ(x÷y) = Logₐx - Logₐy
Answer:
B.
Step-by-step explanation:
The error is in step 3. You cannot use a property of logarithms to prove that same property.
speedrun it
edge 2021